Molecular characterization of Mycobacterium avium subspecies hominissuis isolated from humans, cattle and pigs in the Uganda cattle corridor using VNTR analysis - Muwonge, Adrian; Oloya, James; Kankya, Clovice; Nielsen, Sigrun; Godfroid, Jacques; Skjerve, Eystein; Djønne, Berit; Johansen, Tone B. (Infection, Genetics and Evolution, 2014)
Members of the Mycobacterium avium complex (MAC) cause disease in both human and animals. Their ubiquitous nature makes them both successful microbes and difficult to source track. The precise characterization of MAC species is a fundamental step in epidemiological studies and evaluating of possible reservoirs. This study aimed at identifying and characterizing Mycobacterium avium subsp. hominissuis isolated from human, slaughter cattle and pigs in various parts of the Uganda cattle corridor (UCC) at two temporal points using variable number of tandem repeat (VNTR) analysis. Methods: A total of 46 M. avium isolates; 31 from 997 pigs, 12 from 43 humans biopsies and three from 61 cattle lesions were identified to subspecies level using IS1245 and IS901 PCR, thereafter characterized using VNTR. Twelve loci from two previously described VNTR methods were used and molecular results were analyzed and interpreted using Bionumerics 6.1. Principal findings: 37 of the isolates were identified as M. avium subsp. hominissuis and four as M. avium subsp. avium, while five could not be differentiated, possibly due to mixed infection. There was distinct clustering that coincides with the temporal and spatial differences of the isolates. The isolates from humans and cattle in the North Eastern parts of the UCC shared identical VNTR genotypes. The panel of loci gave an overall discriminatory power of 0.88. Some loci were absent in several isolates, probably reflecting differences in isolates from Uganda/Africa compared to isolates previously analyzed by these methods in Europe and Asia. Conclusions: The findings indicate amolecular difference between M. aviumsubsp. hominissuis isolates from pigs inMubende and cattle and human in the rest of the UCC. Although human and cattle shared VNTR genotypes in the North Eastern parts of the UCC, it is most likely a reflection of a shared environmental source.
Keywords: MATR/MIRU-VNTR; Mycobacterium avium subsp. hominissuis; Human; Cattle; Pigs; Uganda